MXenes for Solar Cells - Yin, Lujie; Li, Yingtao; Yao, Xincheng; Wang, Yanzhou; Jia, Lin; Liu, Qiming; Li, Junshuai; Li, Yali; He, Deyan (Nano-Micro Letters, 2021)
Application of two-dimensional MXene materials in photovoltaics has attracted increasing attention since the first report in 2018 due to their metallic electrical conductivity, high carrier mobility, excellent transparency, tunable work function and superior mechanical property. In this review, all developments and applications of the Ti3C2Tx MXene (here, it is noteworthy that there are still no reports on other MXenes’ application in photovoltaics by far) as additive, electrode and hole/electron transport layer in solar cells are detailedly summarized, and meanwhile, the problems existing in the related studies are also discussed. In view of these problems, some suggestions are given for pushing exploration of the MXenes’ application in solar cells. It is believed that this review can provide a comprehensive and deep understanding into the research status and, moreover, helps widen a new situation for the study of MXenes in photovoltaics. Highlights: 1 This review summarizes applications and developments of MXenes in solar cells by far. 2 The issues needing to be addressed for performance improvement of the related solar cells are discussed. 3 Suggestions are given for pushing exploration of MXenes’ application in solar cells.